Pemberdayaan UMKM Industri Rumahan Melalui Optimalisasi Google Maps sebagai Pemasaran Digital di Kelurahan Mulyorejo Surabaya - Sani Wahyu Chasanah; Nurjanti Takarini (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The digitalization era demands home-based MSMEs in Mulyorejo Subdistrict, Surabaya, enhance visibility through marketing platforms like Google Maps, yet low digital literacy results in only 15% having active profiles. This community service aims to empower 20 MSMEs through Google Maps optimization assistance. Qualitative descriptive methods were applied via door-to-door identification (August 25-October 10, 2025), personal socialization, and individual technical mentoring (October 13-November 21, 2025) covering Google Business Profile creation, location verification, data completion, and product photo uploads. Results show 17 out of 20 MSMEs (85%) successfully activated profiles with 4.2-4.8 star ratings, 25-35% physical visit increase, 70% location search growth, and 15-30% revenue boost in the first month. Personal approach effectively overcomes digital literacy barriers, transforming traditional marketing into independent digital strategies. Google Maps optimization proves essential for strengthening local MSMEs competitiveness, expanding market opportunities, and supporting inclusive economic growth in Mulyorejo Subdistrict.